2016
DOI: 10.1159/000445876
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Habitual Chocolate Consumption to Arterial Stiffness in a Community-Based Sample: Preliminary Findings

Abstract: Background: The consumption of chocolate and cocoa has established cardiovascular benefits. Less is known about the effects of chocolate on arterial stiffness, a marker of subclinical cardiovascular disease. The aim of this study was to investigate whether chocolate intakes are independently associated with pulse wave velocity (PWV), after adjustment for cardiovascular, lifestyle and dietary factors. Methods: Prospective analyses were undertaken on 508 community-dwelling participants (mean age 61 years, 60% wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…56,57,70 Regular chocolate intake has also been associated with a beneficial effect on arterial stiffness, which is involved in the development of systolic hypertension. 71 Results from the large, prospective Cancer Prevention Study II Nutrition Cohort 72 indicated that total flavonoid intake, including flavan-3-ols, was also associated with a lower risk of fatal cardiovascular disease. A metaanalysis of cohort, case-control, and cross-sectional studies reported a 37% lower risk of any cardiovascular disease (five studies), a 31% reduction in the risk of diabetes (one study), and a 29% reduced risk of stroke (three studies) in individuals who consumer higher levels of cocoa and chocolate; however, no significant effect was observed on heart failure (two studies).…”
Section: Effects Of Polyphenols On Cardiometabolic Healthmentioning
confidence: 99%
“…56,57,70 Regular chocolate intake has also been associated with a beneficial effect on arterial stiffness, which is involved in the development of systolic hypertension. 71 Results from the large, prospective Cancer Prevention Study II Nutrition Cohort 72 indicated that total flavonoid intake, including flavan-3-ols, was also associated with a lower risk of fatal cardiovascular disease. A metaanalysis of cohort, case-control, and cross-sectional studies reported a 37% lower risk of any cardiovascular disease (five studies), a 31% reduction in the risk of diabetes (one study), and a 29% reduced risk of stroke (three studies) in individuals who consumer higher levels of cocoa and chocolate; however, no significant effect was observed on heart failure (two studies).…”
Section: Effects Of Polyphenols On Cardiometabolic Healthmentioning
confidence: 99%
“…Regular chocolate intake has beneficial effects on arterial stiffness [150]. Catechins play an important role in the prevention of vascular dysfunction, mainly through the elimination of free radicals in order to prevent lipid oxidation [151]. Meta-analyses have reported that high flavon-3-ols intake can reduce the risk of myocardial infarction [152].…”
Section: Effects Of Catechin/epicatechin and Its Derivatesmentioning
confidence: 99%
“…On the other hand, cocoa consumption did not improve arterial stiffness in patients with cardiovascular risk factors, in a cross-sectional study enrolling 351 subjects [113]. Regular consumption of high-cocoa chocolate also improves vascular function [114], reduces arterial stiffness [104,115], reduces central brachial artery pressures, promoting vascular relaxation of the large, small, and medium-sized peripheral arteries and arterioles, and improves ventricle-arterial coupling [114,116]. The beneficial effects on PWV were demonstrated especially with a long-term and high-dose consumption of cocoa and dark chocolate [117].…”
Section: Cocoa and Chocolatementioning
confidence: 98%
“…Cocoa also contains theobromine or magnesium. Theobromine has vasodilating and antihypertensive effects by inhibiting phosphodiesterase [104]. Magnesium intake also reduces blood pressure, especially in combination with increased potassium and reduced sodium intake [105].…”
Section: Cocoa and Chocolatementioning
confidence: 99%